The Role of Ambition for Freedom in Entrepreneurship Learning as Student Motivation to Become Entrepreneurs: Phenomenological Study on Vocational High School Students in Mojokerto - Dwi Santoso; Irma Suryandari; Sudarmiatin Sudarmiatin; Rizky Firmansyah (Harmony Management: International Journal of Management Science and Business, 2024)
This research aims to understand the role of Ambition for Freedom in entrepreneurship learning as a motivation for students to become entrepreneurs at SMKN 1 JETIS Mojokerto. Using a phenomenological approach, this research explores the subjective experiences of students involved in entrepreneurial learning and how Ambition for Freedom contributes to shaping their motivation to enter the world of entrepreneurship. Data was collected through in-depth interviews with 10 students of SMKN 1 JETIS Mojokerto who had an interest in entrepreneurship, as well as observations of entrepreneurial learning activities in class. Research findings show that students who feel freedom in determining their business tend to have higher motivation to become entrepreneurs, especially because they feel empowered to explore creative ideas and make decisions independently. Ambition for Freedom was found to be an important factor that encourages students to overcome challenges and start businesses. This research contributes to the understanding of how elements of freedom in entrepreneurship education can increase students' interest and readiness for entrepreneurship, and suggests integrating aspects of freedom in the design of the entrepreneurship curriculum at SMKN 1 JETIS Mojokerto.